Encounters in and with Summer Camps-Happy Childhood, Alternative Bildung, or What? - Iuliia Afonkina; Werner Bigell; Valerii Chernik; Torun Granstrøm Ekeland; Tatiana Kuzmicheva; Kirsten Elisabeth Stien; Herbert Zoglowek (MDPI AG, 2021)
Although they commonly are associated with recreation, summer camps for children can be seen as educational arenas that both supplement and challenge school education. Summer camps provide education in a broad sense of bildung. The article aims at describing what is experienced in summer camps and proposes various theoretical frames for these bildung processes. The main focus is on summer camps in Russia, and we interviewed Russian informants who participated in summer camps. The findings were that learning in the camps tends to be non-instrumental, allowing room for play and experimentation for both pupils and teachers. Social learning is marked by collective elements such as camp rituals and spontaneous solidarity, both forming an individual personality. Outdoor activities are important because they connect children to nature and develop a sense of place marked by biophilia. Furthermore, nature's materiality creates a sense of being in the world, which means developing a sense of multiple relational settings, spanning from the materialities of geography, place, and objects to experiencing new social settings in the form of solidarity, ritual, and friendship.